ВПЛИВ ПАЛОМНИЦТВА НА СТАНОВЛЕННЯ ОСОБИСТОСТІ - Слободянюк, С. (Збірник наукових праць Уманського державного педагогічного університету, 2019)
У статті розглядається паломництво, як фактор становлення особистості, як спосіб відновлення пам’яті і віри наших предків. Паломництво допомагає зрозуміти, ким ми є. Орієнтація на традиції дає можливість виховувати справжнього патріота, який опирається на моральні цінності, що є досягненням нашого народу. The given work is devoted to a problem of influence of pilgrimage on a personality formation, memory renewal, spiritual traditions and, first of all, our ancestor’s faith. The author of the work proves that pilgrimage helps to understand who we are, that focus on the traditions gives an opportunity to train a person as a real patriot, who grounds on steady moral values and high spiritual achievements of our people.